CPC-030 Clinical Case of an Adverse Drug Reaction Due to the Administration of an Estrogene/Gestagene Combination Drug. (12th March 2013) - Federica, T; Ruggiero, F; Borin, F; Casnaghi, D; Merlo, M; Trifirò, G; Viganò, M
Abstract : Background: Different European countries have different Summary of Product Characteristics (SmCP) for the same registered drug, which leads to an unequal level of safety information. Purpose: To describe an ADR in a child after administration of Fedra (gestodene + ethinylestradiol) not reported in the Italian SmCP case report. Materials and Methods: The Paediatric Emergency department of our hospital admitted a 15-year-old girl with frequent hand, foot and facial paresthesias on the right side of the body. The patient had been treated with Fedra for 10 days due to menstrual irregularity. Results: At admission, the general status of the patient, monitored by blood, clotting test and imaging studies (CT and brain MRI) appeared within the normal. During the hospitalisation oestro-progestin treatment was suspended with gradual resolution of symptoms and negative neurological follow-up. A report of these ADRs has been submitted to the Agenzia Italiana del Farmaco (AIFA) and to the database of MEAP project (monitoring adverse drug reactions in paediatric patients). Applying the Naranjo algorithm this ADR (frequent hand, foot and facial paresthesias of the right side of the body) was classified as 'possible'. However, in the AIFA database there are 33 ADRs related to the administration of the combo 'gestodene + ethinylestradiol' related to the nervous system, including paresthesias. These reactions are not mentioned in the Italian SmCP, when in the British SmCP they are classified as 'well-known side effect' for the same combination, registered under the trade name of Triminulet. Conclusions: This case study suggests the importance of pointing out all the symptoms, even the minor ones not yet known, especially in the paediatric patients, to better evaluate the safety profile of the drug in this particular population. No conflict of interest.